The Effectiveness of the Online Single Submission Risk-Based Approach (OSS RBA) in Simplifying Business Licensing - Kurniati Handayani Pane, Sri (Jurnal Ilmiah Hukum dan Keadilan, 2026)
In order to enhance national and international competitiveness, the government has undertaken reforms in business licensing through the implementation of an electronic-based licensing system known as Online Single Submission Risk-Based Approach (OSS RBA), as mandated by Law Number 11 of 2020 concerning Job Creation. This study aims to examine the effectiveness of business license issuance through the OSS RBA as a public service innovation, particularly in Palembang City. The research employs a normative juridical method combined with descriptive qualitative research using a case study approach. Data were obtained from laws and regulations, academic journals, and other relevant documents. The findings indicate that the implementation of OSS RBA significantly facilitates business actors, especially Micro and Small Enterprises (MSEs) categorized as low-risk and low–medium risk, as licenses are issued automatically, leading to an increase in the number of business licenses. However, business actors classified as non-MSEs with medium–high and high-risk activities still encounter obstacles, including delays in license issuance caused by a lack of understanding among business actors and inefficiencies in the verification process. Furthermore, the OSS RBA system continues to face challenges related to personal data protection and institutional coordination. Therefore, continuous improvements are required in terms of system development, regulatory frameworks, and capacity building for both business actors and government officials to achieve an effective, transparent, and equitable business licensing system.